Stochastic models in theory of heredity - Ganikhodjaev, Nasir (2012)
We consider linear and nonlinear stochastic models for transmission of blood types and Rhesus factor from parents to their offspring and investigate long run behavior of these models. In this study we will consider an application of the theory of Markov chains and the theory of nonlinear transformations in medicine. It is well known that the gene which determines blood group in humans has three different alleles, A, B, O and that there are four groups of blood, A, B, AB and O. The aim is to investigate the transmission of blood groups from parents to their offspring.